2015
DOI: 10.15395/mkb.v47n2.460
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ekstrak Etanol Propolis Terhadap Aktivitas dan Kapasitas Fagositosis pada Kultur Makrofag yang Diinfeksi Enteropathogenic Escherichia coli (EPEC)

Abstract: AbstrakPenanganan penyakit infeksi diperlukan suatu imunostimulator. Propolis adalah campuran resin yang dikumpulkan lebah dari tumbuh-tumbuhan, digunakan sebagai material isolasi sarang lebah, merupakan bahan yang berpotensi sebagai imunostimulator. Penelitian dilakukan di Laboratorium Penelitian dan Pengujian Terpadu Universitas Gadjah Mada pada Januari-Maret 2013. Penelitian ini bertujuan menganalisis peningkatan aktivitas dan kapasitas fagositosis kultur makrofag yang diberi ekstrak etanol propolis terhada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
1
Order By: Relevance
“…Isolated PBMC transferred into new falcon tube and washed by HBSS (1:1). Macrophages culture was performed according to Herawati et al (2013) briefly, two hundreds microliter of isolated PBMC was dispensed into each well of multidish 24 wells which contains coverslip, and incubated for two hours at 37 o C and 5% CO . Culture supernatants from every well 2 were discarded and washed by HBSS followed by giving 500 µL of complete RPMI (Roswell Park Memorial Institute), incubation was then continued to o 7-10 d at 37 C and 5% Co .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated PBMC transferred into new falcon tube and washed by HBSS (1:1). Macrophages culture was performed according to Herawati et al (2013) briefly, two hundreds microliter of isolated PBMC was dispensed into each well of multidish 24 wells which contains coverslip, and incubated for two hours at 37 o C and 5% CO . Culture supernatants from every well 2 were discarded and washed by HBSS followed by giving 500 µL of complete RPMI (Roswell Park Memorial Institute), incubation was then continued to o 7-10 d at 37 C and 5% Co .…”
Section: Methodsmentioning
confidence: 99%
“…Phagocytosis Activity Examination. Macrophages phagocytosis activity examination againts EPEC was performed in duplicate according to Chairul et al (2009) and Herawati et al (2013). Briefly, 500 µL of lactic acid filtrate or bacteriosins from various concentration dispensed into each well of culture containing mature macrophages followed by adding RPMI to get the final indicated concentration of lactic acid filtrate or bacteriosin in -1 each well 12.5, 6.25, and 3.125 µg mL , including control without filtrate addition.…”
Section: Macrophagesmentioning
confidence: 99%
“…Analysis of the data on day 3 confirmed that the group induced with propolis and those induced with BBG and propolis presented significant differences compared to the control group. This is due to the fact that propolis can increase TLR-2 expression within which TLR activates macrophages with the result that when TLR expression increases the amount of macrophages also rises (Herawati et al, 2015). Moreover, propolis can improve the function of macrophage phagocytes and also enhance the release of interferon-gamma (IFN-γ), interleukin-6 (IL-6), and interleukin-1β (IL-1β) (Hariri, 2019).…”
Section: Journal Ofmentioning
confidence: 99%
“…Bagian perut dibersihkan dengan menggunakan etanol 70% dan dibedah diatas papan bedah. Cairan peritoneum dibuat preparat ulas pada gelas objek dan difiksasi dengan metanol kemudian dilakukan pewarnaan dengan Giemsa (Herawati et al, 2015). Pengamatan dilakukan di bawah mikroskop dengan perbesaran 10x100 kali.…”
Section: Analisis Fagositosis Makrofagunclassified